The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnins.2019.00133
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient Involvement of Insula in Sensorineural Hearing Loss

Abstract: The insular cortex plays an important role in multimodal sensory processing, audio-visual integration and emotion; however, little is known about how the insula is affected by auditory deprivation due to sensorineural hearing loss (SNHL). To address this issue, we used structural and functional magnetic resonance imaging to determine if the neural activity within the insula and its interregional functional connectivity (FC) was disrupted by SNHL and if these alterations were correlated clinical measures of emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 84 publications
(86 reference statements)
1
23
0
Order By: Relevance
“…After the whole-brain analysis, we selected regions of interest that have been consistently implicated in previous neuroimaging studies relating audition, cognition, and dementia (Li et al, 2017;Ren et al, 2018;Xu X.-M. et al, 2019). To define ROI's, we used the Desikan-Killiany atlas, a gyrus-based atlas (Desikan et al, 2006) that has been commonly employed to explore cortical morphometry (Fornito et al, 2013;Jalbrzikowski et al, 2013).…”
Section: Image Processing and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…After the whole-brain analysis, we selected regions of interest that have been consistently implicated in previous neuroimaging studies relating audition, cognition, and dementia (Li et al, 2017;Ren et al, 2018;Xu X.-M. et al, 2019). To define ROI's, we used the Desikan-Killiany atlas, a gyrus-based atlas (Desikan et al, 2006) that has been commonly employed to explore cortical morphometry (Fornito et al, 2013;Jalbrzikowski et al, 2013).…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…Considering that our study explores audition, cognition, NPS and functional impairment, we looked for the main cortical and subcortical brain areas responsible for the following functions in the literature: (i) temporal cortex (e.g., superior, middle, and inferior gyri) was atrophied in a longitudinal hearing impairment study (Lin et al, 2011); (ii) cingulate cortex has been previously related with presbycusis (Husain, 2016;Belkhiria et al, 2019); (iii) amygdala atrophy has been related with neuropsychiatric symptoms in early AD (Poulin et al, 2011); and (iv) structural and functional changes of the insula have been reported in hearing loss patients (Yang et al, 2014;Li et al, 2017;Ren et al, 2018;Xu X.-M. et al, 2019). Other regions such as the hippocampus, thalamus and accumbens areas were included because of their early affection in AD (ten Kate et al, 2018).…”
Section: Regions Of Interest (Rois)mentioning
confidence: 99%
See 2 more Smart Citations
“…Other imaging studies in human subjects have shown that sensorineural hearing loss is associated with a widespread decrease in connectivity in multiple functional brain networks involved in decoding or assessing the meaning of the acoustic environment. These networks include auditory cortical regions and the insula, amygdala, and different cerebellar subregions that combine multimodal sensory information with information on internal state [ 171 , 172 , 173 , 174 ]. For some networks, the lack of connectivity further correlates with measures of speech comprehension, as well as general measures of cognitive performance or affective state.…”
Section: Hearing Loss and Social Isolation Have Extra-auditory Effmentioning
confidence: 99%